2020
DOI: 10.21082/jlittri.v14n4.2008.149-154
|View full text |Cite
|
Sign up to set email alerts
|

DISPERSION PATTERN OF Helopeltis antonii Signoret (HEMIPTERA:MIRIDAE) ON CASHEW PLANTATION

Abstract: <p>ABSTRACT</p><p>Helopeltis antonii is one of the major pests in most cashew growingareas in Indonesia. The pest attacks cashew plants in the nursery and alsoin the fields which caused significant damage. Apart of cashew the insectshave a lot of alternate host plants such as tea, cocoa, neem, pepper,mangoes, jamboes, etc. This research was aimed at investigating thedispersion pattern of H. antonii in cashew plantation. The research wasconducted in smallholder cashew plantation in Ngadirejo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Data of the vertical distribution of H. bradyi and O. javanus was analyzed based on the Poisson dispersion index (DI), negative binomial ( ), and Green Index (GI) by Ludwig and Reynold (1998), reported that insects will form a spatial distribution pattern clump naturally. Siswanto et al, (2008) also stated that Helopeltis has a clump distribution pattern in cashew plantations. Testing of this distribution pattern was through several stages: Ho was rejected from the Poisson distribution thus the insect population was not randomly distributed, the negative binomial test was used to justify if the targeted insect population was clump distributed, and the Green index was used as a further test to determine the grouping degree of the target insect population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data of the vertical distribution of H. bradyi and O. javanus was analyzed based on the Poisson dispersion index (DI), negative binomial ( ), and Green Index (GI) by Ludwig and Reynold (1998), reported that insects will form a spatial distribution pattern clump naturally. Siswanto et al, (2008) also stated that Helopeltis has a clump distribution pattern in cashew plantations. Testing of this distribution pattern was through several stages: Ho was rejected from the Poisson distribution thus the insect population was not randomly distributed, the negative binomial test was used to justify if the targeted insect population was clump distributed, and the Green index was used as a further test to determine the grouping degree of the target insect population.…”
Section: Discussionmentioning
confidence: 99%
“…The pest distribution pattern has been widely investigated as basic information in the study of ecological characteristics and pest control management (Muraleedharan et al, 1988;Wagiman et al, 1998;Siswanto et al, 2008). The vertical distribution pattern of pests is important to be studied because it can affect sampling programs, describe the condition of the population, and can be used to analyze predatorprey relationships (Southwood, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelimpahan populasi dan serangan hama H. hampei mempunyai hubungan yang kuat dengan persentase kehilangan hasil buah kopi di Kabupaten Simalungun, Provinsi Sumatera Utara (Purba et al 2015). Distribusi atau sebaran dan kelimpahan populasi merupakan atribut penting bagi populasi serangga (Siswanto et al 2008). Pengetahuan tentang pola sebaran hama H. hampei sangat penting dalam menyusun metode penarikan contoh yang akurat dan efisien untuk kegiatan pemantauan populasi dan kerusakan buah kopi arabika Gayo.…”
Section: Pendahuluanunclassified
“…These results agree with that obtained by Southwood [41] stated that the higher the variance to mean ratio, the greater the extent of aggregation. Siswanto et al [42] however with different insect species and different host, also suggested that when the population of Helopeltis antonii (Signoret.) (Hemiptera:…”
mentioning
confidence: 99%